PENGARUH HARGA DAN PENJUALAN HAND SANITIZER DITENGAH MARAKNYA WABAH VIRUS COVID-19 TERHADAP TINGKAT PENDAPATAN PADA PT SUMBER ALFARIA TRIJAYA Tbk PROF. DR. HAMKA DI BATURAJA - Iis Sundari; Rini Apriyani (KOLEGIAL, 2021)
The purpose of this study to determine the effect of price and sale of hand sanitizers amidst the covid-19 virus outbreak on income levels at PT Sumber Alfaria Trijaya Tbk Prof. Dr. Hamka in Baturaja. The research method used in this research is descriptive method. The sample in this study were 75 consumers who bought hand sanitizer products. Based on statistical calculations, the equation for multiple linear regression is Y = 3,430 + 0,535X1 + 0,286X2. Based on the results of the calculation of the correlation (r) between the variable price (X1) and sales (X2) will be in line with changes in the level of income at PT Sumber Alfaria Trijaya Tbk Prof. Dr. Hamka in Baturaja (Y) is 0.835. The value of the coefficient of determination (r square) in this study is 0.697 which shows the magnitude of the influence of the price (X1) and sales (X2) variables on the level of income at PT Sumber Alfaria Trijaya Tbk Prof. Dr. Hamka in Baturaja (Y) is 69.7% and the remaining 30.3% is influenced by other variables not examined in this study. The tcount value for the price variable is 5.038> 1.993, then Ho is rejected and Ha is accepted and for the sales variable 3.095> 1.993 Ho is rejected and Ha is accepted, there is an effect of price and sales of hand sanitizers amid the rise of the Covid-19 virus on the income level of PT Sumber Alfaria Trijaya Tbk Prof. Dr. Hamka in Baturaja. The value of Fcount (82.712)> Ftable (3.12) then Ho is rejected and Ha is accepted, meaning that the price and sale of hand sanitizers together have a significant effect on the income level of PT Sumber Alfaria Trijaya Tbk Prof. Dr. Hamka in Baturaja.